Diffusion-Tensor Magnetic Resonance Imaging for Hand and Foot Fibers Location at the Corona Radiata: Comparison with Two Lesion Studies - Lee, Dong-Hoon; Hong, Cheolpyo; Han, Bong-Soo (Frontiers in Human Neuroscience, 2014)
The corticospinal tract is the motor pathway in the human brain, and corona radiata is an important location to diagnose stroke. We detected hand and foot motor fiber tracts in the corona radiata to investigate accurate locations using diffusion tensor imaging and functional imaging. Ten right-handed normal volunteers participated in this study. We used a probabilistic tracking algorithm, a brain normalization method, and functional imaging results to set out ROIs. Moreover, our results were compared to previous results of lesion studies to confirm their accuracy and usefulness. The location measurements were performed in two index types; anteriority index on the basis of the anterior and posterior location of lateral ventricle, laterality index on the basis of the left and right location. The anteriority indices were 56.40/43.2 (hand/foot) at the upper CR and lower CR 40.72/30.90 at the lower CR. The measurements of anteriority and laterality of motor fibers were represented as anteriority index 0.40/0.31 and laterality index 0.60/0.47 (hand/foot). Our results showed that the hand and foot fibers were in good agreements with previous lesion studies. This study and approaches can be used as a standard for diffusion tensor image combined with lesion location studies in patients who need rehabilitation or follow up.